Risk Factors for Severe Illness with 2009 Pandemic Influenza A (H1N1) Virus Infection in China - Yu, Hongjie (Oxford University Press, 2011)
Background. Data on risk factors for severe outcomes from 2009 pandemic influenza A (H1N1) virus infection are limited outside of developed countries. Methods. We reviewed medical charts to collect data from patients hospitalized with laboratory-confirmed 2009 H1N1 infection who were identified across China during the period from September 2009 through February 2010, and we analyzed potential risk factors associated with severe illness (defined as illness requiring intensive care unit admission or resulting in death). Results. Among 9966 case patients, the prevalence of chronic medical conditions (33% vs 14%), pregnancy (15% vs 7%), or obesity (19% vs 14%) was significantly higher in those patients with severe illness than it was in those with less severe disease. In multivariable analyses, among nonpregnant case patients aged ≥2 years, having a chronic medical condition significantly increased the risk of severe outcome among all age groups, and obesity was a risk factor among those <60 years of age. The risk of severe illness among pregnant case patients was significantly higher for those in the second and third trimesters. The risk of severe illness was increased when oseltamivir treatment was initiated ≥5 days after illness onset (odds ratio, 1.42; 95% confidence interval, 1.20–1.67). For persons <60 years of age, the prevalence of obesity among case patients with severe illness was significantly greater than it was among those without severe illness or among the general population. Conclusions. Risk factors for severe 2009 H1N1 illness in China were similar to those observed in developed countries, but there was a lower prevalence of chronic medical conditions and a lower prevalence of obesity. Obesity was a risk factor among case patients <60 years of age. Early initiation of oseltamivir treatment was most beneficial, and there was an increased risk of severe disease when treatment was started ≥5 days after illness onset.